2018
DOI: 10.5664/jcsm.7034
|View full text |Cite
|
Sign up to set email alerts
|

Role of Positive Airway Pressure Therapy for Obstructive Sleep Apnea in Patients With Stroke: A Randomized Controlled Trial

Abstract: Study Objectives: Obstructive sleep apnea (OSA) is an independent risk factor for stroke. The objective of this study was to assess the effect of continuous positive airway pressure (CPAP) treatment on prevention of new vascular events among patients with stroke and OSA. Methods: Consecutive conscious patients presenting with first imaging-confirmed arterial stroke were included, 6 weeks or more after ictus. All patients underwent clinical and polysomnography (PSG) testing. Patients with an apnea-hypopnea inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Primary studies: A further two class II quality studies on the impact of CPAP on measures of vascular risk were published after the systematic search finished and were included [122,123].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Primary studies: A further two class II quality studies on the impact of CPAP on measures of vascular risk were published after the systematic search finished and were included [122,123].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…4 Pilot RCTs have evaluated the effect of CPAP on functional and cognitive outcomes, with mixed results. 6,16,18,[20][21][22][23][24] The majority of trials were conducted in stroke rehabilitation units or a limited number of hospitals, with sample sizes ranging from 30 to 252. Our results now suggest that functional and cognitive outcomes are reasonable targets for larger, adequately powered trials of the effectiveness of CPAP in improving stroke outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25] If treatment with CPAP is shown to improve stroke outcomes in a larger, adequately powered clinical trial, treatment of SDB may be a viable, cost-efficient intervention strategy to improve stroke recovery. [16][17][18][19][20][21][22][23][24][25] If treatment with CPAP is shown to improve stroke outcomes in a larger, adequately powered clinical trial, treatment of SDB may be a viable, cost-efficient intervention strategy to improve stroke recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Spannella et al [8] reported that treatment of obstructive sleep apnea improved not only blood pressure, but also the metabolic profile without any change in weight. Obstructive sleep apnea also increases the predisposition to stroke; and the treatment of obstructive sleep apnea has also been found to reduce chances of future stroke [9]. Thus, there is ample evidence that obesity increases the risk for obstructive sleep apnea, which in turn increases the risk for diabetes mellitus, dyslipidemia, cardiovascular and cerebrovascular morbidity and effective treatment of OSA improves these consequences.…”
mentioning
confidence: 99%